Disrupted Fear and Sadness Recognition in Binge Drinking: A Combined Group and Individual Analysis. (8th August 2019) - Lannoy, Séverine; Benzerouk, Farid; Maurage, Pierre; Barrière, Sarah; Billieux, Joël; Naassila, Mickaël; Kaladjian, Arthur; Gierski, Fabien
Abstract : Background: Binge drinking is a harmful pattern of alcohol consumption, associated with cognitive and cerebral impairments. Indeed, various cognitive processes have been identified as disrupted in binge drinking, ranging from perceptive to executive functions, but emotional processes have conversely been little investigated. Particularly, it is unclear to what extent binge drinkers (BD) present difficulties to recognize and categorize the emotions expressed by other individuals. Such an exploration would, however, offer a more comprehensive view of the deficits associated with alcohol‐related disorders and potentially involved in the maintenance of this harmful habit. Methods: Fifty‐two BD and 42 control participants performed an emotional task assessing the ability to recognize 6 basic emotions (i.e., anger, contempt, disgust, fear, happiness, and sadness). Accuracy score and detection threshold were collected for each emotion. To explore the extent of emotion recognition difficulties, 2 analyses were conducted: (i) classical repeated measures analyses of variance, to compare groups' performance, and (ii) multiple single‐case analyses (i.e., Crawford's t ‐tests), to determine the percentage of BD presenting genuine emotion recognition deficits. Correlations were also performed between alcohol consumption characteristics and emotional recognition scores. Results: BD presented reduced performance for the recognition of fear and sadness. Multiple single cases highlighted that these deficits respectively concerned 21.15 and 15.38% of the binge drinking sample, and the relation between binge drinking and reduced sadness detection was supported by correlational analyses. Conclusions: These findings show that binge drinking is associated with a disrupted processing of emotional stimuli. By identifying heterogeneity in the impairments presented by BD, the present results also underline the usefulness of a combined group and individual Analysis. Abstract : The study investigates the ability to recognize emotional facial expressions in binge drinkers and controls by combining group and individual approaches. Group analyses show that binge drinkers had reduced performance to recognize fear and sadness. Individual analyses specify that these difficulties concern 21.15% and 15.38% of binge drinkers. These results underline the heterogeneity of this population: only a subsample of participants present genuine deficits. Perspectives of these findings are crucial for the identification of "impaired" binge drinkers.